BASIC for beginners - Conley, William E., 1948- (New Delhi. : Galgotia Publications, 1983)
Introduces Basic computer language and explains techniques for using the computer to solve problems in various fields.
Includes index.
Keywords: BASIC (Computer program language); BASIC (Computer program language).; Programming (Computers).; Computers